Technology-enhanced embodied learning: Designing and evaluating a new classroom experience - Ioannou, Marianna; Ioannou, Andri (My University, 2020)
The enactment of embodied learning in the authentic classroom introduces new challenges. The educational system has yet to develop a clear vision or learning design models that would guide the implementation of embodied learning using digital technologies and manipulatives. This study presents an example of a learning design for technology-enhanced embodied learning in an authentic classroom. Three forms of physical embodiment (direct, surrogate and augmented) are enacted using a model consisting of a single educator and rotating across learning stations. The case study takes place in a multidisciplinary lesson around historical information. In this lesson, Year 4 primary school students (i) take virtual tours among the ruins of Archaic kingdoms using mobile VR headsets, (ii) use programmable floor robots to learn about the various occupations people had back then and (iii) create storyboards based on historical information using web-based digital tools. The study evaluates the technology-enhanced embodied learning experience from the perspective of the learners. Data from 34 students demonstrate learning gains, as well as positive perceptions of the learning experience in terms of their relationship with their teammates, their sense of personal development, and the overall classroom orchestration. We conclude with lessons learnt, limitations and suggestions for future work. With this study, we aim to spark a dialogue on how technology-enhanced embodied learning can be successfully enacted in real-world classrooms, highlighting the need for more studies in the intersection of technology, design and pedagogy.
Keywords: Classroom orchestration; Embodied learning; Learning design; Technology integration; Technology-enhanced learning